1HRDP: as a new administrative tool / Junaida Ismail ... [et al.] - Ismail, Junaida; Ahmad Zawawi, Azlyn; Azizan, Intan Syahriza; Rusli, Noorayuni; Mohd Yusoff, Noorlailahusna; Ramli, Shahriza Ilyana (2020)
“1 Hour Report Duty Procedure (HRDP)” is a web link that contains report duty procedure with information and document attachments that are needed during the report duty process of new lecturers at UiTM Kedah. The web link aims to shorten the time taken to complete the registration process of new lecturers in UiTM Kedah. With the improved procedure, lecturers are guided to complete the reporting process within an hour. The procedure is designed in the form of an easy-to-understand and navigable via external link. The link also includes necessary documents and forms needed in the registration process. Through this web link, new lecturers are able to access important information to complete report duty process such as reporting procedures, person in charge, and they can also download relevant documents / forms. The target of this link is to ensure that the report duty process can be shortened so that the process will be more organized and systematic. “1 Hour Report Duty Procedure (HRDP)” web link is easily accessible and navigable via external links on computers or smartphones.